IoT Solutions for Energy Efficiency: A Bibliometric Analysis of Environmental Impact and Resource Management (West Science Interdisciplinary Studies, 2024)
This bibliometric analysis explores the scope and dynamics of Internet of Things (IoT) research with a focus on energy efficiency, environmental impact, and resource management. Using data sourced from Scopus and visualized through VOSviewer, the study maps out the evolution of research themes, highlights interdisciplinary collaboration, and discusses the integration challenges and policy implications of IoT technologies. The analysis identifies a significant shift from foundational technological issues to applications that enhance sustainable development and address global energy demands. Despite challenges such as implementation costs, security concerns, and environmental impacts associated with IoT devices, the potential of IoT in promoting energy efficiency and sustainability is profound. The study also emphasizes the need for robust policies and international cooperation to fully leverage IoT benefits in addressing environmental and energy management challenges. Future research directions are suggested to further explore the integration of IoT with renewable energy sources and to enhance the sustainability of IoT systems.